The Push Factors of Entrepreneurship: Examining Unemployment, Job Dissatisfaction, and Economic Conditions as Drivers of MSME Owners' Decision to Become Entrepreneurs in North Jakarta - Suryawirawan, Okto Aditya; Suhermin, Suhermin; Pribadiyono, Pribadiyono; Yuliati, Eka; Azizah, Muftiyatul (Transpublika Publisher, 2025)
Despite various government initiatives to promote entrepreneurship, Indonesia's entrepreneurial growth remains low, with a minimal increase in entrepreneurial rates and one of the lowest rankings in Southeast Asia. Prior research on entrepreneurial intentions in Indonesia has primarily focused on pull factors, while the role of push factors remains underexplored. The objective of this research is to examine how push factors, including unemployment, job dissatisfaction, and unfavorable economic conditions on the entrepreneurial intention and behavior of MSME owners situated in North Jakarta. This study employs a non-probability purposive sampling technique, targeting MSME owners in North Jakarta as respondents. Data from 80 MSME owners were collected to achieve a statistical power of 80%. The study utilizes Partial Least Squares (PLS) to analyze the data. The results indicate that unemployment has a significant positive effect on entrepreneurial intention but does not directly influence entrepreneurial behavior. Job dissatisfaction does not significantly affect either entrepreneurial intention or entrepreneurial behavior. Economic situation has a strong positive influence on entrepreneurial intention but does not directly impact entrepreneurial behavior. Entrepreneurial intention significantly influences entrepreneurial behavior. Entrepreneurial intention mediates the relationship between unemployment and entrepreneurial behavior, as well as between economic situation and entrepreneurial behavior, while no significant mediation effect is found for job dissatisfaction. This study highlights the need for policy support to strengthen entrepreneurial intention among unemployed individuals, as it drives entrepreneurial behavior.